N-Acetyl-L-Cysteine modulates indium-tin oxide nanoparticles-caused interstitial lung diseases in male rats through oxidative stress-activated apoptosis and autophagy - Yanzi Zhao; Yujing Niu; Xuefei Wang; Peng Wan; Zhanfei Ma; Jian Sun; Shoufang Jiang; Ling Xue; Nan Liu (Ecotoxicology and Environmental Safety)
Indium-tin oxide nanoparticles (Nano-ITO) are widely used in various applications as infrared shielding materials, which increase the risk of occupational exposure. According to reports, Nano-ITO can cause indium lung disease in occupational exposed workers, but the specific mechanism of Nano-ITO-induced pulmonary toxicity remains unclear. In this study, 50 8-week-old male Sprague-Dawley rats were divided into five groups (10 rats in each group) as follows: control group (physiological saline), 1.2 mg/kg Nano-ITO group, 6 mg/kg Nano-ITO group, N-Acetyl-L-Cysteine (NAC) control group (200 mg/kg), and NAC + Nano-ITO group (200 mg/kg NAC intraperitoneal injection, after 1.5 h, 6 mg/kg Nano-ITO intratracheal instillation), twice a week for 12 weeks. Pathological and ultrastructural changes in the rat lung tissue, immunofluorescence assays, immunohistochemistry, protein and mRNA levels of apoptosis- and autophagy-related genes were measured. The levels of ROS, MDA, H2O2, and LDH, and the activities of T-AOC and SOD, were determined using oxidative stress assay kits. The results showed that Nano-ITO caused strong pulmonary inflammation, pulmonary alveolar proteinosis, and pulmonary interstitial fibrosis. In addition, Nano-ITO-induced oxidative stress in rat lungs presented as increased levels of ROS and H2O2 in the lungs, increased LDH and MDA levels, SOD and T-AOC activity in BALF, and activation of the Nrf2/NQO1/HO-1 signaling pathway. Intriguingly, Nano-ITO significantly increased the protein expression of microtubule-associated protein light chain 3 (LC3-II), the protein levels of autophagy-related genes 5 (ATG5), and Beclin-1 (BECN1), and reduced the protein levels of phosphatidylinositol 3-kinase (PI3K) in lung tissues. In addition, transmission electron microscopy (TEM) showed a significant increase in autophagic vesicles in the cytoplasm of lungs treated with Nano-ITO, indicating that Nano-ITO induces autophagy in rat lungs. Moreover, apoptosis also participates in Nano-ITO-induced pulmonary injury in a synchronous manner, as evidenced by the enhancement of TUNEL-positive signals and activation of the apoptosis pathway (Bax and Bcl-2 positive proportions). NAC supplementation restored most of the pathological structural features of rat lung tissue to their physiological range and effectively weakened apoptosis, as demonstrated by the notable reductions in TUNEL, Bax, and Bcl-2 protein expression levels in the lungs. Although autophagy was detected in the lungs of rats in the Nano-ITO and NAC + Nano-ITO groups, we discovered that NAC could rescue the expression of ATG5 and BECN1 induced by Nano-ITO, thus indicating that exposure to Nano-ITO promotes pulmonary apoptosis and autophagy by mediating oxidative stress. These results indicate that Nano-ITO can cause pulmonary injury by inducing oxidative stress, which activates apoptosis and autophagy, ultimately leading to alveolar proteinosis and interstitial fibrosis.